Collaborative Brazilian pediatric renal transplant registry (CoBrazPed-RTx): A report from 2004 to 2018 - de Souza, Vandrea Carla; Garcia, Clotilde Druck; Pestana, Jose Medina; Stopa Martins, Suelen Bianca; Porini Custódio, Luciana de Fátima; Bittencourt, Viviane; Rohde, Roberta; Simões Pires, Izadora; de Camargo, Maria Fernanda; Koch Nogueira, Paulo; Feltran, Luciana de Santis; Esmeraldo, Ronaldo de Matos; et al. (Wiley, 2019)
The Brazilian collaborative registry for pediatric renal transplantation began in 2004 as a multicenter initiative aimed at analyzing, reporting, and disseminating the results of pediatric renal transplantation in Brazil. Data from all pediatric renal transplants performed from January 2004 to May 2018 at the 13 participating centers were analyzed. A total of 2744 pediatric renal transplants were performed in the thirteen participating centers. The median age at transplantation was 12.2 years, with the majority being male recipients (56%). The main underlying diseases were CAKUT (40.5%) and glomerulopathy (28%). 1981 (72%) of the grafts were from deceased donors (DD). Graft survival at one year (censored by death) was 94% in the live donor group (LD) and 91% in the DD group (log-rank test P < 0.01). The patient’s survival at one and 5 years was 97% and 95% for the LD group and 96% and 93% for the DD group (log-rank test P = 0.02). The graft loss rate was 19% (n = 517), more frequently caused by vascular thrombosis (n = 102) and chronic graft nephropathy (n = 90). DD recipients had 1.6 (1.0-2.2) times greater chance of death and 1.5 (1.2-1.8) times greater chance of graft loss compared to LD recipients. The mortality rate was 5.4% (n = 148), mainly due to infection (n = 69) and cardiovascular disease (n = 28). The results of this collaborative pediatric renal transplant record are comparable to other international registries, although we still have a high infection rate as a cause of death.
Keywords: kidney transplantation; pediatric nephrology; registry